PENGARUH PEMBAYANGAN ANTAR MASSA DAN TIPE FASAD TERHADAP EFEKTIVITAS PENERAPAN PANEL FOTOVOLTAIK PADA FASAD RUSUNAWA NAGRAK JAKARTA - -, Evelyn; Ritva Santoso, Amirani (Jurnal Riset Arsitektur, 2023)
Abstract – The sun is one of the most important and largest sources of energy for the earth. The energy emittedby the sun can be utilized both actively and passively. Solar cells or photovoltaics are used to convert solarradiation into electrical energy, which is known as active utilization.Rusunawa (Rumah Susun Sederhana Sewa)is a facility to provide affordable housing for people with low income. The target demographic create a needsfor clean and affordable energy, which can be overcomed by implementing solar panels.The current type of Rusunawa being built is high-rise buildings with over 15 levels. This new type ofbuilding decreases the roof space while increasing the facade area. As a result, photovoltaics panels must beinstalled on the building's façade. The goal of this research is to determine the effectivity of implementing solarpanels on the facade of Rusunawa Nagrak, in correlation to the tenant’s energy cost savings, as well as todetermine standard coefficients/ values so that the findings can be applied in the future to building with similartypologies with slight adjistments.This is an experimental-quantitative type research done with the help of Rhinoceros, Grasshopper, andLadybug software to find the most optimal photovoltaic panel configuration for the use of Rusunawa NagrakTower 1-5.Keyword: Government Subsidized High-Rise Housing, Photovoltaic Panel, Masses Configuration Shading,Building Façade, Cilincing Jakarta.